GE_GERICHTE C/17833/2018 vom 25. Juni 2019 - GE Cour de justice (2019)
PROTECTION DE L'UNION CONJUGALE ; LOGEMENT DE LA FAMILLE ; OBLIGATION D'ENTRETIEN ; ENFANT ; REVENU HYPOTHÉTIQUE | CC.176.al1.let1; CC.176.al1.let2; CC.176.al3; CC.276; CC.276a; CC.285.al2